Identification of a novel large deletion in a patient with severe factor V deficiency using an in‐house F5 MLPA assay. (30th November 2014) - Nuzzo, F.; Paraboschi, E. M.; Straniero, L.; Pavlova, A.; Duga, S.; Castoldi, E.
Summary Factor V (FV) deficiency is a rare autosomal recessive bleeding disorder caused by mutations in the F5 gene. FV‐deficient patients in whom no mutation or only one mutation is found may harbour large gene rearrangements, which are not detected by conventional mutation screening strategies. The aim of this study was to develop and validate a multiplex ligation‐dependent probe amplification (MLPA) assay for the detection of large deletions and duplications in the F5 gene. Twenty‐two MLPA probes targeting 19 of the 25 exons and the upstream and downstream regions of the F5 gene were designed and tested in 10 normal controls, a patient with a known heterozygous deletion of F5 exons 1–7 (positive control) and 14 genetically unexplained FV‐deficient patients. MLPA results were confirmed by digital PCR on a QuantStudio™ 3D Digital PCR System. The F5‐specific probes yielded a reproducible peak profile in normal controls, correctly detected the known deletion in the positive control and suggested the presence of a novel deletion of exons 9–10 in a patient with undetectable FV levels and only one identified mutation. Follow‐up by chip‐based digital PCR, long‐range PCR and direct sequencing confirmed that this patient carried a heterozygous F5 deletion of 1823 bp extending from intron 8 to intron 10. Bioinformatics sequence analysis pinpointed repetitive elements that might have originated the deletion. In conclusion, we have developed and validated an MLPA assay for the detection of gross F5 gene rearrangements. This assay may represent a valuable tool for the molecular diagnosis of FV deficiency.